Recapture of lynx individual B132 in the Trentino province, Italy - Brugnoli A (Forest@, 2010)
In February 2010, B132 - a male lynx born in 2006 in north-eastern Switzerland - was recaptured in a box trap set above Molveno Lake, in Brenta Massif eastern slopes, and fit with a new GPS/GSM radiocollar by staff members of the Forest and Wildlife Service of the Autonomous Province of Trento. His 2008 dispersal into the Adamello-Brenta Natural Park area in the Trentino province was the furthest one ever documented outside of Scandinavia for a Eurasian lynx. The complete recovery of the lynx in the entire Alpine arc, after 40 years since the first reintroduction, will be a long-term task, and documentation of B132’s dispersal and spatial behaviour is of crucial interest in this respect.